THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, AND BRAND AWARENESS TO PURCHASE INTENTION AT RESTAURANT KEDAIKOE BANJARMASIN - Marcelina Dinata; Kezia Caroline; J.E Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to analyze the factors influencing consumers’ purchase intention toward restaurant Kedaikoe in Banjarmasin. This research employs a quantitative approach using a survey method by distributing questionnaires to respondents who have visited or are familiar with restaurant Kedaikoe. The data were analyzed using statistical analysis to examine the relationship between the research variables and consumers’ purchase intention. The results indicate that the examined factors influence consumers’ purchase intention, which ultimately affects the number of visits to the restaurant. This study is expected to provide insights for restaurant management in better product qualities, service qualities and brand awareness to increase purchase intention and attract more visitors.